KATA MAJEMUK BAHASA MELAYU RIAU DIALEK TEREMPA - Hasmahyati '; Hasnah Faizah AR; Auzar ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study discusses the compound word riau dialek of the Malay language Terempa. This study also discusses the type of compound words, the prosess of formation of compound words, and the meaning of compound words. This research uses descriptive method. The data in this study are utterances informant containing compound words. The purpose this research is to describe what are the types of compound words Riau dialect of the Malay language Terempa, how the process of formation of compound words dialect Terempa Riau Malay language, and what meaning of compound words Terempa Riau Malay language. The results of this research as a contribution for further research on the compound.Keywords: Compound, Dialect of Malay, Terempa.